Proteomics analysis of pyrene biodegradation using strain Mycobacterium sp. 16F. Issue 1 (31st December 2022) - Guo, Peng; Jin, Longguo; Cui, Weitong; Yang, Yan; Cheng, Yanjun; Wang, Daoping; Pan, Yinghong; Jin, Jinghua
ABSTRACT: Mycobacterium sp. 16 F can degrade 94% of pyrene (20 ppm) in 4 days. To investigate its pyrene degradation mechanism, proteomic changes were analyzed using two-dimensional differential gel electrophoresis (2DE-DIGE). Comparative analysis of differential proteins revealed 91 differentially expressed protein spots after pyrene exposure. Among these, 65 spots were identified as 57 proteins. Further analysis revealed that 13 spots were involved in the pyrene degradation pathway, and most of these were dioxygenases and dehydrogenases. Further, 16 up-regulated expression protein spots were associated with four pathways that may be related to pyrene degradation. Bioinformatics analysis further revealed that the pentose phosphate and glycolytic pathways led to the production of amino acids and nucleotide precursors in pyrene-induced cells. The metabolites from these processes then entered the shikimate pathway via the β-ketoadipate pathway in conjunction with the pyrene degradation pathway. This study provides a new model for the pyrene degradation pathway in Mycobacteria. Abbreviations: PPP, pentose phosphate pathway; ED-EMP, Entner-Doudoroff pathway and Embden-Meyerhof-Parnas pathway; E4P, erythrose-4-phosphate; PEP, phosphoenol-pyruvate; PAL, phenylalanine ammonia-lyase; SucCoA, succinyl-CoA; AcCoA, acetyl-CoA; TCA, tricarboxylic acid cycle.